1987
DOI: 10.1177/08959374870010022301
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite and Carbonated Apatite as Models for the Dissolution Behavior of Human Dental Enamel

Abstract: t is now well-established that kinetic aspects as well as considerations based solely on solubilities and thermodynamic driving forces should be taken into account while one is attempting to understand the mechanism of dental caries. In the present study, kinetic comparisons of the dissolution of hydroxyapatite, carbonated apatite, and ground human dental enamel have been made in order that the appropriateness of these synthetic phases as enamel dissolution models can be assessed. Specific additives used to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 28 publications
(40 reference statements)
1
23
0
1
Order By: Relevance
“…Numerous studies [1, 3-6, 10, 11, 40] have attempted to determine the factors controlling the chemical stability of apatites. The effects of foreign ions such as carbonate, fluoride, and strontium upon the crystalline properties and the dissolution tendency of apatites have been extensively studied [1,5,6,[41][42][43], but no quantitative relationship between one or more independent variables and the solubility behavior of apatites has been previously demonstrated. In our earlier study, the MES of the CAPs was shown to correlate well with the crystallinity parameter (FWHM of 002 peak) [8].…”
Section: Mes Distribution Measurementsmentioning
confidence: 99%
“…Numerous studies [1, 3-6, 10, 11, 40] have attempted to determine the factors controlling the chemical stability of apatites. The effects of foreign ions such as carbonate, fluoride, and strontium upon the crystalline properties and the dissolution tendency of apatites have been extensively studied [1,5,6,[41][42][43], but no quantitative relationship between one or more independent variables and the solubility behavior of apatites has been previously demonstrated. In our earlier study, the MES of the CAPs was shown to correlate well with the crystallinity parameter (FWHM of 002 peak) [8].…”
Section: Mes Distribution Measurementsmentioning
confidence: 99%
“…Carbonated apatites (CAPs) have been widely investigated because they have been considered to be excellent models for studying the physicochemical properties of biological hard tissues [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. From the physical chemical standpoint, CAPs closely parallel biominerals (e.g., dental enamel and bone mineral) in terms of dissolution [2,5], structure [1,6,17,18], thermal treatment [11], and solubility behavior [12,19].…”
Section: Introductionmentioning
confidence: 99%
“…From the physical chemical standpoint, CAPs closely parallel biominerals (e.g., dental enamel and bone mineral) in terms of dissolution [2,5], structure [1,6,17,18], thermal treatment [11], and solubility behavior [12,19].…”
Section: Introductionmentioning
confidence: 99%
“…224 The kinetics of enamel dissolution has also been found to be strongly influenced by the presence of impurities released to the solution during the reaction. 225 In view of this, depending on minor effects of impurities or changes in the experimental conditions, an unexpected pH versus t trend can be triggered, signifying deviations from the standard precipitation pathways. Solutions that are particularly prone to exhibit this sensitivity are those that lie toward the middle of the metastability zone, between the levels of saturation (S ¼ 1) and critical supersaturation (S > 19.5).…”
mentioning
confidence: 99%